Effects of Climate Change on Poultry Production in Benue State, Nigeria - Ezihe, J.A.C.; Ali, A.; Ivom, G. A. (Archives of Business Research, 2020)
The study assessed the effects of climate change on poultry production in Benue State, Nigeria. One hundred and seventy nine (179) poultry farmers were interviewed to elicit relevant information in line with the objectives of the study. Descriptive statistics and inferential statistical tools were used for data analysis. Findings revealed that Majority (46.8%) of all the poultry farmers fall within 21-40 years age bracket .This results imply that poultry farmers in the area were above the dependent age. The average age of the respondents was 39.1 years and within the economically active age range. Majority of (52.5%) of the respondents were females and 47.5% were males. This means that poultry production is gender sensitive. The result showed that respondents have one level of education to the other, an indication that school leavers were no longer waiting for white kola jobs rather than engaged themselves in poultry production in the study area. The average start-up capital of the respondents was found to be N85,542, this may be due to the fact that majority of the respondents operate in small scale. Close to half (48.6%) of the respondents practiced intensive system of poultry production in the study area. with the mean years of awareness as 10.51. The findings further revealed that 90.9% of the respondents agreed that they are aware of climate change; this indicates that the majority of the poultry farmers in the study area have noticed variation in climatic elements. 85.9% of the respondents all agreed that temperature fluctuate in the study area. 72.6% of the respondents observed increased sunshine intensity in the study area and 76.3% agreed that distribution of rainfall follows normal distribution. 80.5% of the respondents agreed that global warming has effect on poultry production respectively. Inferential statistics shows that there is a significant relationship between respondents’ socio – economic characteristics and perception of poultry farmers on effects of climate change on poultry production since p > 0.05 (r = 0.544, p= 0.000). It is recommended extension agents and other development agencies need to educate the poultry farmers more about the effects posed by climate change on poultry production and intensify awareness campaign to poultry farmers on how to reduce the effects of climate change on poultry production.